Role of Thrips Omnivory and Their Aggregation Pheromone on Multitrophic Interactions Between Sweet Pepper Plants, Aphids, and Hoverflies - Vaello, Teresa; Pineda, Ana; Marcos-García, Mª Ángeles (Frontiers in Ecology and Evolution, 2019)
In complex food webs, plants are commonly attacked by multiple herbivorous species, affecting the preference and performance of other herbivores and natural enemies. The role of omnivorous insects in ecosystems may be more complex because of the consumption of both plant and animal organisms. However, the effect of omnivorous insects on herbivores and natural enemies, has received little attention so far. The main goal of this study was to investigate whether the dual herbivore interaction between aphids and thrips, an omnivorous pest, on a sweet pepper system, may affect different trophic levels, from plant and aphid performance until the third trophic level, i.e., preference and performance of the predatory hoverfly Sphaerophoria rueppellii. Additionally, we tested whether the aggregation pheromone of the thrips Frankliniella occidentalis, could disturb the oviposition behavior of the predatory hoverfly. Our results show that the presence of thrips decreases host plant and aphid performance. Furthermore, despite not affecting syrphid larval performance, thrips presence reduces fecundity of the adults that emerge from those larvae. Additionally, we observed that syrphids avoid ovipositing on plants with either thrips or thrips aggregation pheromone. The present study reveals how the presence of thrips or a semiochemical compound related to thrips, can impact the behavior and performance of an aphidophagous predator.